ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN - I Wayan Putrana; Majid Wajdi; Komang Wahyulia Saraswati (Forum Manajemen STIMI Handayani Denpasar, 2022)
The purpose of this study was to determine the effect of service quality (tangible, reliability, responsiveness, assurance and empathy) caring for the satisfaction of new customers in telecommunications companies in Denpasar. The research method used is quantitative. The sample in this study were 119 people taken using the purposive sampling method. Data was collected by distributing questionnaires and then processed with SPSS. The analysis shows that tangible, reliability, responsiveness, assurance and empathy have positive effects on customer satisfaction. Hypothesis testing partially and simultaneously of the independent variables is significant, because the significance value <0.05. The coefficient of determination shows that the ability of tangible variables, reliability, responsiveness, assurance and empathy in explaining customer satisfaction is 62.6%. This means that Service Quality has an influence on Customer Satisfaction